STUDY ON LOW VELOCITY IMPACT CHARACTERISTICS OF HYBRID COMPOSITE HONEYCOMB SANDWICH STRUCTURE - ZHANG ChaoFeng; DU WeiZhong; WANG WeiLi (Jixie qiangdu)
The impact resistance of composite honeycomb sandwich structure is studied by means of experiment and finite element analysis. The three-dimensional progressive failure criterion is established based on the VUMAT subroutine, and the accuracy of the simulation model is verified by experiments. The accurate simulation model is used to further study the impact resistance of honeycomb sandwich structure under different parameters. The results show that when the impact energy is lower than a certain value, the impact peak force increases with the increase of impact energy, and when the impact energy exceeds this value, the impact peak force will be stable; the smaller the impactor diameter is, the smaller the impact peak force is, the greater the absorption energy of honeycomb sandwich structure is; the increase of skin thickness can enhance the impact resistance of honeycomb sandwich structure, but the skin thickness has a greater impact on the energy absorption characteristics small.